USING DISCRETE WAVELET ANALYSIS OF VIBRATION SIGNAL FOR DETECTION OF ELECTRICAL MACHINES’ DEFECTS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
The paper proposes a method for establishing the presence of several of the most common defects of rotating electric machines of alternating current using discrete wavelet transform of their vibration signal. It is shown that discrete wavelet transform is one of the most effective methods of pre-processing vibration signals formed from the operation of rotating electric machines. The choice of optimal maternal wavelet functions for each of the considered defects according to the sensitivity parameter is theoretically substantiated, and frequency bands are determined, which should be analyzed for their detection analysis of wavelet transform coefficients. The adequacy of the theoretical conclusions is experimentally confirmed.
Keywords: Technical condition; Diagnostics; Electric machine; Defect; Wavelet transform